NUCLEAR STRIKE AGAINST HIROSHIMA AND NAGASAKI. WARCRIME, THAT COULD BE AVOIDED - N. P. Parkhitko (Vestnik MGIMO-Universiteta)
The article focuses on the research of the consequences of the US nuclear bombings of Japanese cities in August 6th and 9th 1945. Military, political and psychological aspects, that were crucial for American military planning at the latest stage of the Second World War are taken into consideration. Also the problems of the new reality in the global policy of that period, which made it possible to demonstrate the military power in such a destructive way, are investigated. The author offers some logical alternatives to the real circumstances of the 6thAugust 1945, including both implementing and non-implementing of the nuclear weapons. The author also offers some new conception of the bipolarity considering the «A-bomb factor» in the international relations, which was critical since August 1945 till August 1949. The very fact of the using the most destructive and powerful weapon, developed after the Germans' capitulation but before the capitulation of Japan, corresponds with the political concept, offered by K. Clausevitz in early 19th century. The approach to the problem, advocated by the German military theorist was in details researched in the article. Using some historical and political methodology, the author criticizes the realization of this concept in August 1945th and offers some alternatives in the historical retrospective. Acknowledging, on the whole, the necessity of demonstration of the newest weapon by the United States in global political aspect, the author reveals a number of targets, which seem more optimal for this goal. Bombing of peaceful cities, which caused inadmissible civil losses, is characterized by the author as military crime.